State Financial Institutions : Mandates, Governance, and Beyond - Rudolph, Heinz P. (2012)
There is no doubt that on average the performance of state financial institutions around the world has been below the lowest expectations. Lack of governance, management skills, regulation, and transparency, and misguided incentives have contributed to discredit these institutions for supporting the development of local financial markets. However, the pro-active role that some state financial institutions have played in the recent crisis in allocating credit to sectors cyclically not attractive for commercial banks has brought back the question of whether some state ownership in the banking system would be preferable. This paper analyzes the experience of four state financial institutions that have performed relatively well in the past: Canada's Business Development Bank, Chile's BancoEstado, South Africa's Development Bank of Southern Africa, and Finland's Finnvera plc. The author finds that these institutions have different checks and balances to mitigate eventual mismanagement of resources. The author also finds that little progress has been made in measuring the policy performance of these institutions.